Moderating Role of Social Support in Internal Locus of Control and Grit Among Undergraduate Students - Hitipeuw, Imanuel; Setianingrum, Margaretta Erna; Murwani, Fulgentius Danardana; Eva, Nur (Universitas PGRI Yogyakarta, 2025)
Grit plays a pivotal role in supporting students’ academic success, especially when navigating challenges in higher education. This study examined the relationship of internal locus of control on grit with social support as a moderator among undergraduate students. Conducted among 423 undergraduate students from six universities in Malang City, East Java, the study utilized Cluster and Random Sampling techniques. Data were gathered using Indonesian-adapted scales: the Triarchic Model of Grit, Academic Locus of Control, and Multidimensional Perceived Social Support. Data analysis was performed using the Moderated Regression Analysis (MRA) method. The results showed that internal locus of control has a significant influence on students' grit, with social support serving as a moderating variable (F Change = 16.245, p = 0.01). This finding suggests that social support enhances the effect of internal locus of control on students' grit, referring to the assistance and encouragement individuals receive from their social networks. Keywords: grit, internal locus of control, social support, undergraduate students, moderation